Documentation of the Method Used by Norges Bank for Estimating Implied Forward Interest Rates - Gaute Myklebust (Norges Bank, 2005)
Forward interest rates are an important indicator for monetary policy. They are commonly used, both by central banks and market participants, to gain information about market expectations of future interest rates. Forward rates in the short term are traded directly in the market, but for longer horizons they must be derived implicitly from the yield curve. In this paper we will briefly comment on the method used by Norges Bank for estimating implied forward interest rates. Previously, Kloster (2000) has described this in more detail. However, the Bank has made some adjustments to the procedure described in Kloster's article. Hence, this paper is an update and a summary of the method currently used. The paper is structured as follows: Firstly, we will comment on the selection of instruments. There are in general two alternative types of instruments suitable for estimating implied forward rates in the Norwegian market. One is the market for government securities, while the other is the swap market. Secondly, we will give a brief description of the estimation procedure, which is based on the Svensson method or the extended Nelson and Siegel method. Finally, we will comment on the adjustments we make for risk premia. There are a number of potential risk premia in the estimated forward rates. However, the corrections we make are only minor, and relate to the credit risk element in the forward rates derived from the swap market.
hdl:11250/2508112
Keywords: 330